LITERAL TRANSLATION AS DOMINANT PROCEDURE FOUND IN "ENCANTO" MOVIE SUBTITLE - Putu Armitha Widiyanthi; I Gusti Agung Sri Rwa Jayantini; Ni Made Verayanti Utami (Journal of Language and Literature, 2022)
The literal translation employed in the subtitle of the movie "Encanto" was the primary focus of this study. The purpose of the study is to identify the main categories of translation procedures utilized in the movie subtitle for "Encanto" and to discuss how the literal translation procedures are applied. In this study, the qualitative descriptive approach was applied. The data for the study was derived from the movie’s subtitle, "Encanto." The data were acquired through viewing the motion, reading the script, assessing many sorts of translation techniques, correlating the dialogue to the script, classifying and recognizing words, phrases, and clauses, then lastly selecting and noting the various categories of data. The information was seen and examined by utilizing Newmark's (1988) theory of translation procedures. There is one dominant type found in this research, such as literal translation, procedures about 24 data are found in this research. Literal procedure the subtitle translated into the closest meaning.